Environmental monitoring in Sidary bay (Corfu Island) using Remote Sensing and GIS techniques. - Evelpidou, N.; Vassilopoulos, A.; Vaiopoulos, D.; Mantas, I. (Congress of Remote Sensing for Environmental Monitoring, GIS Applications, and Geology II, 2002)
This paper is a preliminary study of an extensive project that will take place at Corfu island (Northern island of Ionian Sea), involving the municipality of Esperion and the Remote Sensing Laboratory (University of Athens). The project’s purpose is to estimate the erosion progress at Sidari bay’s (North part of Corfu island) coastal zone, due to wave activity. Sidari area consists of Neogene formations, which are extremely vulnerable. Moreover, wave impact is also of high energy, causing subsidence of the coastal line. Through this project, our team is developing a GIS database that holds information, deriving from existing maps, bibliographical references, and climatological logs, related to geology, geomorphology and environmental parameters. Apart from those data, aerial photography stereo observation and extensive D-GPS fieldwork resulted to continual coastline monitoring and GIS database updating, for a period of 26 and 5 years, respectively. Project’s conclusions are based on quantitative and spatial analysis through GIS, giving answers on the erosion’s rate, the erosion’s impact on human activities and structures, and finally an estimation on Sidari’s coastal zone future morphology.